Weed Management in Apples - Jeffrey G. Williamson (EDIS)
Revised! These 3-4 page fruit and nut fact-sheets by Jeffrey G. Williamson from the Weed Management Guide have been updated. They provide tables of chemical weed control recommendations. Published by UF Department of Horticultural Sciences, November 2007.